The Latin bloc into thinking Francisco Garcia Calderon - Aljovin de losada, Cristobal (2013)
The article analyzes Don Francisco García Calderon Rey’s understanding of the relationship between Latin countries and other group of countries, especially Anglo-Saxon countries (The United States of America) from the early XXth century to First World War, the time when ideas changed. During those years, García Calderon postulates a vision that Latin countries lead by France were confronted by Anglo-Saxons, Germans and the Japanese. His geopolitical understanding was based on his definition of “the” Latin race, which excludes the non-European population in Latin America.